A satellite soil moisture– and radar rainfall–based methodology for slope-scale seepage–stability modelling of rainfall-induced landslides - Apiniti Jotisankasa; Punpim Puttaraksa Mapiam; Monton Methaprayun; Washirawat Praphatsorn; Kritanai Torsri; Soravis Supavetch; Suttisak Soralump; Jonathan Linnebach; Thom Bogaard (Landslides, 2026)

Modeling the Effects of Gap Cuts on Stand-Level Resilience in Financial and Carbon Sequestration Contexts - Jonathan Fibich; Alexander Lange; Thomas Clemen; Dominik Thom; Thomas Knoke (Environmental Management, 2026)
Climate change is amplifying disturbances in Central European forests, making resilience a key concept in forest management planning. Yet, the impacts and trade-offs of practices regarded as resilience-enhancing, such as pre-rotation age establishment of young trees in canopy gaps remain insufficiently quantified. Here, we adapt a recent quantification framework, using the post-disturbance recovery time of the present value of a given ecosystem service ( E S ) as stand-level resilience metric. Our novel, Monte-Carlo Simulation-based (MCS) approach models time series for two E S (net revenues and aboveground carbon sequestration) to quantify the impacts of disturbances under different gap-cut regimes, which we compare against a clear-cut baseline. Gap-cuts can notably enhance resilience, reducing average recovery times by up to 6.6 years (-15.7%) in the financial and 3.3 years (-21.3%) in the carbon sequestration context. Concerning the financial aspects, some gap-cut regimes small in gap size and late in timing could enhance resilience without associated losses in soil expectation value. However, most regimes, although dominating in the resilience metric, were associated with opportunity costs. These costs were less pronounced for carbon sequestration. We conclude that gap-cut induced regeneration can enhance resilience in both financial and carbon contexts, but their optimal timing and size depends on the prioritized ecosystem service. As the complexity of forest stand representations is inherently limited by our MCS-approach, further research should refine forest-value estimation through neural networks and mechanistic models, enabling richer representations of growth and disturbance dynamics and more detailed management regimes.

Correction: On the Relationship Between Aquatic CO2 Concentration and Ecosystem Fluxes in Some of the World’s Key Wetland Types - Jessica L. Richardson; Ankur R. Desai; Jonathan Thom; Kim Lindgren; Hjalmar Laudon; Matthias Peichl; Mats Nilsson; Audrey Campeau; Järvi Järveoja; Peter Hawman; Deepak R. Mishra; Dontrece Smith; et al. (Wetlands, 2024)

Improving parameterization of an evapotranspiration estimation model with eddy covariance measurements for a regional irrigation scheduling program - Ammara Talib; Ankur R. Desai; Jingyi Huang; Jonathan Thom; John C. Panuska; Paul.C. Stoy (Agricultural and Forest Meteorology, 2024)

On the Relationship Between Aquatic CO2 Concentration and Ecosystem Fluxes in Some of the World’s Key Wetland Types - Jessica L. Richardson; Ankur R. Desai; Jonathan Thom; Kim Lindgren; Hjalmar Laudon; Matthias Peichl; Mats Nilsson; Audrey Campeau; Järvi Järveoja; Peter Hawman; Deepak R. Mishra; Dontrece Smith; et al. (Wetlands, 2024)

Measuring pH of skim milk and milk permeate at ultra-high temperatures at laboratory and pilot scale - Tugce Aydogdu; James A. O'Mahony; Thom Huppertz; Jonathan B. Magan; Noel A. McCarthy (International Dairy Journal, 2023)

An exploratory study to investigate the association between age, physical activity, femoral trochlear cartilage thickness and biomarkers of tissue metabolism in adult males - Harry M. Roberts; Claire L. Griffith-McGeever; Julian A. Owen; Lewis Angell; Jonathan P. Moore; Jeanette M. Thom (European Journal of Applied Physiology, 2021)
Purpose To investigate the association between age, physical activity, femoral trochlear cartilage thickness and biomarkers of tissue metabolism in a cross-sectional sample of adult males. This study utilizes several emerging biomarkers that have been associated with early joint degenerative changes; serum COMP (cartilage oligomeric matrix protein), HA (hyaluronan) and lubricin. Methods Eighty-one males (age: mean (range): 43(18–70) years; body mass index: 25.2 (21.0–30.6) kg/m 2 ) volunteered. Resting serum COMP, HA and lubricin concentrations were determined via commercially available enzyme-linked immunosorbent assay (ELISA) and femoral trochlear cartilage thickness via supra-patellar ultrasound imaging. Physical activity levels were assessed using questionnaires. Statistical analyses were performed using correlation and regression analyses. Results Age was correlated with lateral trochlear cartilage thickness ( r = − 0.372; p < 0.01) and serum COMP ( r = 0.342; p < 0.01). 7-day physical activity was correlated with serum COMP ( r = 0.357, p < 0.01), and 12-month physical activity with both lateral trochlear cartilage thickness ( r = 0.340, p = 0.01) and serum HA ( r = 0.296, p < 0.05). Regression analyses revealed that age significantly accounted for the variability in lateral cartilage thickness and serum COMP, following the adjustment for potential cofounders. However, the association between age and lateral trochlear cartilage thickness was not moderated by physical activity levels (all p > 0.05). Conclusion This study indicates that older age may be associated with thinner lateral trochlear cartilage and higher cartilage turnover. Being physically active may also be positive for lateral trochlear cartilage thickness. However, overall, both age and physical activity level only account for a small amount of the variability in cartilage thickness and serum biomarkers.

Pantropical variability in tree crown allometry - Grace Jopaul Loubota Panzou; Adeline Fayolle; Tommaso Jucker; Oliver L. Phillips; Stephanie Bohlman; Lindsay F. Banin; Simon L. Lewis; Kofi Affum‐Baffoe; Luciana F. Alves; Cécile Antin; Eric Arets; Luzmila Arroyo; et al. (Global Ecology and Biogeography, 2021)
Aim Tree crowns determine light interception, carbon and water exchange. Thus, understanding the factors causing tree crown allometry to vary at the tree and stand level matters greatly for the development of future vegetation modelling and for the calibration of remote sensing products. Nevertheless, we know little about large‐scale variation and determinants in tropical tree crown allometry. In this study, we explored the continental variation in scaling exponents of site‐specific crown allometry and assessed their relationships with environmental and stand‐level variables in the tropics. Location Global tropics. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 87,737 trees distributed among 245 forest and savanna sites across the tropics, we fitted site‐specific allometric relationships between crown dimensions (crown depth, diameter and volume) and stem diameter using power‐law models. Stand‐level and environmental drivers of crown allometric relationships were assessed at pantropical and continental scales. Results The scaling exponents of allometric relationships between stem diameter and crown dimensions were higher in savannas than in forests. We identified that continental crown models were better than pantropical crown models and that continental differences in crown allometric relationships were driven by both stand‐level (wood density) and environmental (precipitation, cation exchange capacity and soil texture) variables for both tropical biomes. For a given diameter, forest trees from Asia and savanna trees from Australia had smaller crown dimensions than trees in Africa and America, with crown volumes for some Asian forest trees being smaller than those of trees in African forests. Main conclusions Our results provide new insight into geographical variability, with large continental differences in tropical tree crown allometry that were driven by stand‐level and environmental variables. They have implications for the assessment of ecosystem function and for the monitoring of woody biomass by remote sensing techniques in the global tropics.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

The effect of aerobic walking and lower body resistance exercise on serum COMP and hyaluronan, in both males and females - Harry M. Roberts; Jonathan P. Moore; Jeanette M. Thom (European Journal of Applied Physiology, 2018)

The effect of vigorous running and cycling on serum COMP, lubricin, and femoral cartilage thickness: a pilot study - Harry M. Roberts; Jonathan P. Moore; Claire L. Griffith-McGeever; Matthew B. Fortes; Jeanette M. Thom (European Journal of Applied Physiology, 2016)

Persistence of aquatic refugia between flow pulses in a dryland river system(Cooper Creek, Australia) - Stephen K. Hamilton; Stuart E. Bunn; Martin C. Thoms; Jonathan C. Marshall (Limnology and Oceanography, 2005)
In many dryland rivers with intermittent flow, relatively deep segments of the river channel serve as refugia for aquatic life during protracted intervals between flows. Semipermanent channel segments are known as waterholes in the semiarid Cooper Creek system of western Queensland. Fractional water loss by evaporation was estimated in 15 Cooper waterholes from the increase in conservative ion (Na + and Cl − ) concentrations and independently from evaporative fractionation of oxygen and hydrogen isotopes in water. The major solute chemistry and isotope results indicated that evaporative water loss controlled the water levels between flows and that the surface waters were effectively isolated from underlying groundwater that had a distinctive chemical and isotopic composition. Fractional water loss rates combined with stage‐volume relationships for each basin showed a mean evaporative loss rate of 2.1 m yr −1 ; during that time (April‐October 2002), pan evaporation averaged 2.5 m yr −1 . Site‐specific extrapolation of those estimated evaporative loss rates indicated that the waterholes would dry to 10% of their bankfull volumes in 6‐23 months, although those estimates were based on sampling in 2002, when pan evaporation rates were 18% higher than the long‐term mean. These persistence times show the importance of occasional, irregular flow pulses in sustaining these aquatic refugia; the desiccation of waterholes could become more common if future water withdrawals reduce the frequency and intensity of river flows to the point where they occur less often than annually.